Cartografia social: instrumento de luta e resistência no enfrentamento dos problemas socioambientais na reserva extrativista Marinha da Prainha do Canto Verde, Beberibe - Ceará - Costa, Natane Oliveira da (2016)
The Social Cartography appears as a cartographic knowledge in the industry that has a great social appeal mainly due to the fact of empowering traditional peoples in territorial risk, assisting them in demarcation of their own limits for hunting, fishing, extraction, etc. In this context, this research aims to systematize a set of technical and methodological procedures from community practical experience, which facilitates the development of social maps from Extractive Marine Reserve of Prainha do Canto Verde, representing a diagnosis of the socio-environmental conflicts and community proposals for solving the problems that were found. Therefore, we held:I) a participatory diagnosis demonstrating the cultural and environmental characteristics of the community; II) it was represented cartographically, using methodologies of Social Cartography, traditional territories, noting elements and relevant aspects of the community, and II) it was led through the use of geo subsidies for the community of Prainha do Canto Verde so that they could be able to practice a territorial management following the precepts of environmental conservation. Regarding the methodological procedures, the theoretical framework was based on studies of (ACSELRAD, 2008; ALMEIDA, 2008; CHAPIN, 2005; POPAYAN, 2005; CARVALHO, 2014), among others. While methodological approach, the Social Cartography has foundations in research-action-participation in this case being also considered the territory of concepts and landscape. Participatory research seeks to empower people who historically had been excluded from the construction of information about their realities process. The social mapping was constituted by eight workshops, namely, I) General Assembly; II) Participatory Diagnosis; II) Net of Problems; IV) Potential; V) Map of Fishing Resources; VI) Propositional Zoning, VII) The Maps and Settings and VIII) Validation of the Maps. Elaborate maps were meant to provide the word to community through a change in ownership, production and use of cartography. If before the maps were produced by the dominant groups to demarcate and control territory, it is now important to understand that the maps can and should be built and used by social groups as an instrument of resistance to different forms of domination. It is believed that the actions taken contribute to the fortification of the fight before the socio-environmental conflicts at the local level. It is noteworthy that activities were coordinated and organized by environmental analysts from Chico Mendes Institute of Biodiversity Conservation – ICMbio and Geoprocessing Laboratory – LABOCART, associated with the Geography Department of Universidade Federal do Ceará – UFC.